Genealogy of Islamic Fatayat Politics in the Era of Soekarno and Soeharto: a Feminist Studies on Organizational History - Wafiroh, Nihayatul (Jurnal Perempuan, 2014)
Indonesian Muslim women had long been an inseparable part from political activities since the colonial period to present era. During colonial era, although they did not work formally under certain Islamic women’s organizations, they made real contributions to the women’s political movement in Indonesia since they formed women’s branches of existing mass organizations. Fatayat, this organization is the sister branch of the largest Islamic organizations in Indonesia: Nahdlatul Ulama. This paper narrates that the involvement of Fatayat in politics had its historical and genealogical roots since Soekarno era. Sukarno facilitated Fatayat to develop power capacity in politics. However, during Soeharto era Fatayat experienced a setback due to New Order’s control toward women’s organization with its “ibuism” ideology. In order to maintain its existence, Fatayat decided to collaborate with government by incorporating state’s program such as PKK, Posyandu into their activities while alos made network with national and international funding organization.